Bilateral and metastatic pheochromocytoma in a 11-year-old child: A case report - Takwa Mili; Said Jlidi; Yosra Ben Ahmed; Awatef charieg; Meryem Oumaya; Maryem Marzouki; Intissar Chibani; Faouzi Nouira (Elsevier, 2023)
Introduction: Pheochromocytomas are rare neuroendocrine tumors. Bilateral and metastatic pheochromocytoma in children is even rarer. We report a case of a 11-year-old girl presenting with malignant hypertension related to a bilateral and metastatic pheochromocytoma. Case presentation: We report the case of a 11-year-old male girl who presented with malignant hypertension. CT scan findings and urinary catecholamines dosage were consistent with bilateral pheochromocytoma. After stabilization of blood pressure, the patient underwent cortex sparing bilateral adrenalectomy and removal of two metastatic lymph nodes. Post-operatively, she showed complete resolution of hypertension and no steroids were required. Conclusion: Pheochromocytoma should be considered as a possible diagnosis in children presenting with malignant hypertension. Stabilize blood pressure is important part in the preoperative period. Adrenal sparing surgery showed promising outcomes in treating cases of bilateral disease.